Description of Daily Nutritional Intake of Pregnant Women in Temanggung District, Central Java, Indonesia - M. Zen Rahfiludin; Yudhy Dharmawan (Journal of Public Health for Tropical and Coastal Region, 2019)
Background: The nutritional status of pregnant women are affected by daily nutritional intake. Daily nutritional intake during pregnancy depends on total macronutrient intake and micronutrient intake. The aim of the study is to describe daily nutritional intake from pregnant women in Temanggung,Central Java, Indonesia.Method: This study was conducted from September – December 2016 in Temanggung. This was a cross sectional study and the respondents were recruited using purposive sampling technique. Total sample of this study were 60 pregnant women. Intakes of macronutrients (Energy, and Protein), and micronutrients were calculated based on Food Frequency Questionnaire (FFQ) Semi Quantitative and using Nutrisoft software, Demographic data were obtained by interviewing.Results Of the total 60 pregnant women, 40 (66,7%) were unemployed. The majority of educational level of the respondents  (48,3%) were Junior High School.  The mean gestational age were 6,70 ± 1,109 months. The mean intake of energy in 60 pregnant women was 2153,9833 ± 369 kcalConclusion: The majority of pregnant women in this study have adequate intake of both macro and micronutrient besides iron and folic acid.